Akibat Hukum Penandatanganan Surat Kuasa Jual Mutlak Sebelum Debitor Mengalami Kredit Macet - Tiyas Putri Megawati; Aulia Dwi Ramadhanti; Faizah Nur Fahmida (Jurnal Ilmu Kenotariatan, 2024)
Credit Agreements are always followed by the provision of guarantees, one of which is land that charged with Dependent Rights or by granting Power of Attorney to Sell from Debtors to Creditors. Referring to the Instruction of the Minister of Home Affairs Number 14/1982 about the Prohibition of the Use of Absolute Power of Attorney, the signing of a Power of Attorney to Sell that made unconditional without terms and condition about discontinuation and contain absolute clauses is expressly prohibited. This opens up risk opportunities in the future, especially for the Debtor. In reality, the signing of a Power of Attorney to Sell in conjunction with credit agreement at the beginning is still widely found. In this study, the author examines the topic using normative juridical methods or legal research. The conclusion of this study shows that the signing of the Absolute Power of Attorney to Sell at the beginning before a bad credit occurs causes the power of attorney being null and void, because it doesn't meet one of the objective requirements of the agreement, especially about a lawful cause as in Article 1320 paragraph (4) of the Civil Code. In terms of the Absolute Power of Attorney to Sell, the Debtor entitled legal protection both in preventive or repressive ways. KEYWORDS : Absolute Power of Attorney to Sell, Legal Consequences, Non-Perfoming Loan (NPL)